1993
DOI: 10.1002/bio.1170080108
|View full text |Cite
|
Sign up to set email alerts
|

Separation of pH, dilution, lonic strength and chemical matrix effects for biological monitoring of urines with the Microtox® test using nicotine, cotinine and reference urines

Abstract: The aim was to investigate the factors influencing light emission from Photobacterium phosphoreum in the Microtox test to interpret bioassay results for urine. Four reference urines were assessed as reference materials for the bioassay. Nicotine and cotinine were investigated as urinary markers for tobacco exposure. The optimum luminescence conditions were: 1.85%-3.25% NaCl, 0.33-0.58 mol/L ionic strength, and pH 5.8-6.7. Low pH values and high concentration of toxic trace metals were important factors in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
(16 reference statements)
1
14
0
Order By: Relevance
“…The acute test dilution medium was 2.0% saline. Extensive testing (4) showed that the optimum bioluminescence at 5, 15 and 25 min occurred over the sodium chloride range of 1.9-3.3% (ionic strengths of 0.32-0.58 M) with EC 50 values of 1.3% and 5.0%. Thus sample sizes in toxicity testing should be kept small relative to growth medium.…”
Section: Acute Toxicity Experimentsmentioning
confidence: 99%
See 3 more Smart Citations
“…The acute test dilution medium was 2.0% saline. Extensive testing (4) showed that the optimum bioluminescence at 5, 15 and 25 min occurred over the sodium chloride range of 1.9-3.3% (ionic strengths of 0.32-0.58 M) with EC 50 values of 1.3% and 5.0%. Thus sample sizes in toxicity testing should be kept small relative to growth medium.…”
Section: Acute Toxicity Experimentsmentioning
confidence: 99%
“…The effective concentration at which the luminescence is 50% that of the control (EC 50 ) is the diagnostic parameter for the acute test. The 5 to 30 min EC 50 for the acute test (the Microtox test) is correlated to Draize Test results for eye irritation, the acute LD 50 for Salmo gairdneri, Daphnia, Spirillum, and the 14-day LD 50 for guppies (Poecilia reticulata) (4). The chronic test 24-h Lowest Observed Effective Concentration (LOEC) is correlated to 7-day Ceriodaphnia dubia data (3).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The bacterium is standardized by storing and transporting it as a freeze-dried powder that is reconstituted into a saline growth medium at 153C at the time of the analysis. Our research group has published on the variables that a!ect the test Que Hee, 1992, 1993;Chen and Que Hee, 1995) and on some applications (Chou and Que Hee, 1992, 1993, 1994aChen and Que Hee, 1995;Que Hee, 1997). The present study explores the dependence of light output on viable cell number, the e!ects of dust on the Microtox test and cell viability, how the viability of the cells is a!ected after spills, and how spills can be sampled.…”
Section: Introductionmentioning
confidence: 96%